Magnanimity: A Screenplay Exploring the Unconditional Forgiveness - Alvin Gabriel Joadianto; Ribut Basuki (Kata Kita: Journal of Language, Literature, and Teaching, 2024)
This creative thesis focuses on unconditional forgiveness, exploring the question of how a son can really hate his father. The first theory, Parental Alienation Syndrome, answers how a child can hate one parent because of the insult from the other parent. The child affected by Parental Alienation Syndrome has eight distinct symptoms. Furthermore, this creative thesis wants to explore how the son can forgive his father without the father’s repentance. Employing the Process Model of Forgiveness, the thesis shows the step-by-step journey of forgiveness without any repentance. Both theories will be applied in the creative work, a screenplay. The screenplay is about a victim of Parental Alienation Syndrome haunted by his hatred of his father ever since his parents' separation. The protagonist experiences the three symptoms of Parental Alienation Syndrome. Moreover, he will go through each stage of the Process Model of Forgiveness until achieving reconciliation with his father.